The human medial temporal lobe processes online representations of complex objects. - Barense, MD; Gaffan, D; Graham, K (2007)
There has been considerable debate as to whether structures in the medial temporal lobe (MTL) support both memory and perception, in particular whether the perirhinal cortex may be involved in the perceptual discrimination of complex objects with a large number of overlapping features. Similar experiments testing the discrimination of blended images have obtained contradictory findings, and it remains possible that reported deficits in object perception are due to subtle learning in controls, but not patients. To address this issue, a series of trial-unique object "oddity" tasks, in which subjects selected the odd stimulus from a visual array, were administered to amnesic patients with either selective bilateral damage to the hippocampus or more extensive damage to MTL regions, including the perirhinal cortex. Whereas patients with damage limited to the hippocampus performed similarly to controls on all conditions, patients with perirhinal damage were significantly impaired when the task required discrimination between objects with a large number of features in common. By contrast, when the same stimuli could be discriminated using simple visual features, patients with perirhinal damage performed normally. These results are consistent with a theoretical view which holds that rostral inferotemporal cortical regions, including perirhinal cortex, represent the complex conjunctions of stimulus features necessary for both perception and memory of objects.